The role of propranolol as a radiosensitizer in gastric cancer treatment - Liao XH; Chaudhary P; Qiu G; Che XM; Fan L (Dove Medical Press, 2018)
Xinhua Liao, Prakash Chaudhary, Guanglin Qiu, Xiangming Che, Lin Fan General Surgery Department, First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, China Purpose: The National Comprehensive Cancer Network guidelines indicate that radiotherapy in gastric cancer shows limited effectiveness at reducing the growth of gastric cancer. Therefore, enhancing the sensitivity and effect of radiotherapy with propranolol, a β-adrenoceptor antagonist, could reduce tumor growth. The role of propranolol as a radiosensitizer has not been adequately studied; therefore, the purpose of the present study is to evaluate the effect of propranolol as a radiosensitizer against gastric cancer in vivo. Methods: Sixty-four male nude mice bearing tumor xenografts were randomly divided into four groups. Cell culture was performed using the human gastric adenocarcinoma cell line SGC-7901. Mice with tumor xenografts were treated with propranolol, isoproterenol, and radiation. The data for tumor weight and volume were obtained for statistical analyses. Furthermore, the expression levels of COX-2, NF-κB, VEGF, and EGFR were examined using immunohistochemical techniques and Western blotting.Results: The growth in the volume and weight of the tumor was lower in mouse models treated with propranolol and radiation therapy compared to the other groups. Decreased expression of NF-κB was also observed in treatment groups where both propranolol and radiation were used, leading to the reduction of COX-2, EGFR, and VEGF expression compared to that in the other groups.Conclusion: The present study indicated that propranolol potentiates the antitumor effects of radiotherapy in gastric cancer by inhibiting NF-κB expression and its downstream genes: VEGF, EGFR, and COX-2. Keywords: propranolol, radiosensitizer, gastric cancer, radiation therapy